"Let's talk about money": how do poor older people finance their healthcare in rural Ghana? A qualitative study - Williams Agyemang-Duah; Charles Peprah; Prince Peprah (BMC, 2019)
Abstract Background Older people utilise more healthcare services and are likely to incur higher healthcare expenditure, however, data on their healthcare financing mechanisms are scarce in low-and middle- income countries including Ghana. In this study, we aimed at exploring how poor older people finance their healthcare in rural Ghana. Methods We conducted in-depth interviews and focus group discussions with 60 study participants comprising 30 poor older people, 15 healthcare providers and 15 caregivers in Atwima Nwabiagya District of Ghana. Data were analysed using thematic analytical framework and presented based on an a posteriori inductive reduction approach. Results The study revealed that poor older people finance their healthcare through personal income, family support, Livelihood Empowerment Against Poverty grants and National Health Insurance Scheme subscription. It was also found that poor older people spent between GH¢ 20 and 250 on drugs, laboratory test and hospitalisation anytime they access a healthcare facility. Conclusion The findings contribute to our understanding of how poor older people finance their healthcare in rural Ghana. We argue that health stakeholders should strengthen healthcare financing mechanisms for poor older people for optimal healthcare use.